Alumina carrier as well as preparation method and application thereof

By adding inorganic carbon species to the alumina and performing specific surface treatment, the density and type of oxygen-containing groups on the surface of the alumina support are improved, and the problem of uneven distribution of active metals of the existing alumina support catalysts is solved, and higher metal utilization and catalytic performance are achieved.

CN119500087AActive Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311028071.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-25
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

The existing alumina support has a small number of oxygen-containing groups, a low density and a single type, which leads to uneven distribution of catalyst active metals, making it difficult to meet the requirements of high metal utilization, high performance and long life.

Method used

Inorganic carbon species are added to the alumina, and the types, quantity and density of oxygen-containing groups on the surface of the alumina are increased by surface treatment methods such as heat treatment, crystallization, oxidation, alkalization, and irradiation.

Benefits of technology

The total content of oxygen-containing groups on the surface of the alumina support is significantly improved, especially the hydroxyl content, the dispersion form and dispersion of metal active components are improved, and the reaction performance of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004397115010000151
    Figure BDA0004397115010000151
  • Figure BDA0004397115010000161
    Figure BDA0004397115010000161
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and particularly relates to an alumina carrier as well as a preparation method and application thereof. The surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.15-5mmol / m < 2 >. Wherein the oxygen-containing group is at least one of hydroxyl, carboxyl and lactone group; the specific surface area of the alumina carrier is 10-150m < 2 > / g. The types, the number and the density of oxygen-containing groups on the surface of the obtained carrier are improved, and various index requirements of various supported catalysts on dispersion forms and dispersion degrees of different metal active components in the field of petrochemical engineering can be well met; and the carrier also has the characteristics of low bulk density, high water absorption rate, large pore volume and large average pore size, has a gain effect on uniform distribution of active metal components in the catalyst loading process, and has extremely high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and specifically relates to an alumina carrier and a preparation method and application thereof. Background Art

[0002] Alumina is widely used in the field of petrochemicals as a carrier of supported catalysts because of its easy availability, low cost, good thermal stability, corrosion resistance, wear resistance, and insulation. Industrial alumina carriers are generally obtained by molding alumina powders such as pseudo-boehmite powder and quick-release alumina powder. Different types of reactions have different requirements for the physicochemical properties of alumina carriers. It is generally believed that the physical properties of the powder raw materials, molding aids, and molding parameters will affect the pore volume, pore size, specific surface area, strength, thermal stability, acidity and alkalinity of the alumina carrier, and thus affect the performance of the subsequently prepared catalyst. There have been many related studies and reports on regulating the physical parameters of alumina carriers by optimizing the alumina powder refining process and alumina molding methods.

[0003] CN109420528A discloses a modified alumina carrier and a preparation method thereof, wherein an alumina precursor is uniformly mixed with a furfuryl alcohol solution of a certain concentration, a peptizing agent is then added, and the mixture is kneaded into a plastic body, which is then formed, dried, and calcined to obtain an alumina carrier having uniform carbon distribution, high carbon content, high weak acid distribution, and high mechanical strength.

[0004] CN105983443A discloses an alumina carrier with a bimodal pore structure and a preparation method thereof, wherein hydrated alumina is mixed with synthetic cellulose, a boron-containing compound and a powdered polymer, molded and calcined to obtain an alumina carrier that can be used in the field of catalytic hydrogenation and has a bimodal pore structure, large pore volume and pore diameter, good mechanical strength and a simple preparation process.

[0005] CN115957821A discloses a γ-alumina carrier and a preparation method thereof. A hydrothermal method is used to form a crown ether lanthanum organic ligand formed by a crown ether organic long chain and a soluble lanthanum salt, which is uniformly grafted onto the surface of the pore structure of the γ-alumina material, and the structure is modified to protect the surface hydroxyl groups, inhibit sintering and phase change, and reduce the damage of high temperature to the microporous structure; and the organic ligand can reduce the cation vacancies in the γ-alumina structure, reduce the probability of interaction between anions and cation vacancies, so that it still has a stable crystal structure under high temperature environmental conditions.

[0006] Existing literature shows that the number or density of hydroxyl groups on the surface of alumina affects the dispersion form and dispersion degree of metal active components. For example, the literature (ACS Catalysis, 2023, 13, 4, 2277-2285) prepared three γ-Al2O3 carriers with different OH contents and OH densities by calcining the pseudo-boehmite carrier at different temperatures. It was found that the final dispersion degree of Ag on the γ-Al2O3 surface depends on the OH content, and the dispersion speed depends on the OH density. The literature (Nature Communications, 2020, 11, 1, 529) found that increasing the number of terminal hydroxyl groups of γ-Al2O3 can greatly improve the dispersion of Ag on its surface and even present single atomic dispersion.

[0007] The existing technical solutions result in a small number of oxygen-containing groups on the surface of the alumina carrier, low density, and a single type. At the same time, there are few methods and means for regulation, resulting in low uniformity of distribution of active metals in the subsequent catalyst preparation and poor thickness controllability, making it difficult to achieve the requirements of high metal utilization, high performance, and long life. At the same time, the preparation process of the alumina carrier is long and complicated, and there is a problem that the properties of different batches of alumina carriers obtained by the same method and conditions are unstable.

[0008] Therefore, there is still a need to develop an alumina carrier with a simple preparation method, controllable surface oxygen-containing groups and stable properties, which can be suitable for a variety of catalytic reactions. Summary of the invention

[0009] In view of the technical problems existing in the prior art, the purpose of the present invention is to provide an alumina carrier and a preparation method and application thereof. The inventors of the present invention have found through research that by adding inorganic carbon species to alumina and then subjecting it to surface treatment such as heat treatment (different from calcination), crystallization, oxidation, alkalization, and irradiation treatment, the surface of alumina can have hydroxyl groups and other oxygen-containing groups other than hydroxyl groups. The types, quantity and density of oxygen-containing groups on the surface of the obtained carrier are improved, which can well meet the various index requirements of various types of supported catalysts in the field of petrochemical industry for the dispersion form and dispersion degree of different metal active components; and the carrier also has the characteristics of low bulk density, high water absorption rate, large pore volume and average pore size, which has a benefit effect on the uniform distribution of active metal components in the catalyst loading process, and has extremely high application value.

[0010] The first aspect of the present invention is to provide an alumina carrier, wherein the surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.15-5 mmol / m 2 ; wherein the oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 10-150m 2 / g, preferably 15-80m2 / g.

[0011] In a preferred embodiment of the present invention, the specific surface area of ​​the alumina carrier is preferably 15-80 m 2 / g, such as 15, 30, 40, 50, 60, 70, 80m 2 / g, and any two values ​​or any interval between any two values.

[0012] In a preferred embodiment of the present invention, the content of the hydroxyl group is 3-60 mmol / g.

[0013] In a preferred embodiment of the present invention, the content of the carboxyl group is 3-50 mmol / g.

[0014] In a preferred embodiment of the present invention, the content of the lactone group is 3-40 mmol / g.

[0015] According to a preferred embodiment of the present invention, the content of the hydroxyl group is 3-60 mmol / g, the content of the carboxyl group is 3-50 mmol / g; and the content of the lactone group is 3-40 mmol / g.

[0016] According to the present invention, the technical effect of regulating the amount of oxygen-containing groups on the surface of alumina can be achieved by adopting the preparation method of the present invention. When the alumina carrier is used as a catalyst carrier in the future, it can realize the improvement of the dispersion of the loaded metal and the diversification of the coordination form, thereby improving and improving the catalyst reaction performance. Because different oxygen-containing groups have different properties, their effects on the dispersion of metals and catalytic performance are also inconsistent. There is no unified understanding of the interaction between different oxygen-containing groups and metal precursors and the size of metal particles. Generally speaking, the stronger the "anchoring" effect of the carrier on the metal particles, the higher its dispersion, but the metal may be coated by the carrier or the coordination is too stable, so that its adsorption activation ability for the reactant molecules is significantly weakened or disappears, and the catalytic performance is reduced instead. Therefore, for some catalysts, it is not that the higher the metal dispersion, the better the catalytic performance. In the present invention, the alumina carrier can be specifically regulated and matched according to the subsequent required preparation of the catalyst and the reaction that needs to be adapted.

[0017] According to a preferred embodiment of the present invention, the density of oxygen-containing groups on the surface of the alumina carrier is preferably 0.3-3 mmol / m 2 , for example 0.3, 0.5, 1, 1.5, 2, 2.5, 3 mmol / m 2 , and any two values ​​or any interval between any two values.

[0018] According to a preferred embodiment of the present invention, the content of hydroxyl group is 3-60 mmol / g, for example, 3, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 mmol / g, and any two values ​​or any interval between any two values.

[0019] According to a preferred embodiment of the present invention, the carboxyl content is 3-50 mmol / g, for example 3, 10, 15, 20, 25, 30, 35, 40, 45, 50 mmol / g, and any two values ​​or any interval between any two values.

[0020] According to a preferred embodiment of the present invention, the content of the lactone group is 3-40 mmol / g, for example 3, 10, 15, 20, 25, 30, 35, 40 mmol / g, and any two values ​​or any interval between any two values.

[0021] In a preferred embodiment of the present invention, the alumina support contains alumina and optionally an inorganic compound other than alumina.

[0022] According to the present invention, the inorganic compound can be selected from a wide range. In a preferred embodiment of the present invention, the inorganic compound is preferably selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite.

[0023] According to the present invention, the mass ratio of the inorganic compound to the aluminum oxide can be selected within a wide range. In a preferred embodiment of the present invention, the mass ratio of the inorganic compound to the aluminum oxide is (0-30):100, preferably (0-28):100, for example, 0, 5, 10, 15, 20, 23, 28 and the ratio of any two values ​​or any interval between any two values ​​to 100.

[0024] In a preferred embodiment of the present invention, the alumina carrier has at least one of the following characteristics: the water absorption rate of the alumina carrier is 50%-200%; and / or the strength of the alumina carrier is 30-200Nm; and / or the bulk density of the alumina carrier is 0.4-0.8g / ml; and / or the pore volume of the alumina carrier is 0.6-1.5ml / g.

[0025] The detection method of the above characteristics of the alumina carrier in the present invention can adopt the detection method described in the specific implementation method section, including but not limited to the detection method in the specific implementation method section.

[0026] In a preferred embodiment of the present invention, the alumina carrier contains alumina and carbide.

[0027] In a preferred embodiment of the present invention, based on the total weight of the alumina carrier being 100 wt%, the content of the alumina is 50-98 wt%.

[0028] In a preferred embodiment of the present invention, the alumina carrier is prepared by the following preparation method, which comprises:

[0029] The raw materials including alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina are granulated and surface treated to obtain the alumina carrier;

[0030] Wherein, the surface treatment method is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment;

[0031] The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; the oxidation is oxidation by an oxidant.

[0032] The second aspect of the present invention is to provide a method for preparing an alumina carrier, the preparation method comprising:

[0033] The raw materials including alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina are granulated and surface treated to obtain the alumina carrier;

[0034] Wherein, the surface treatment method is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment;

[0035] The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; the oxidation is oxidation by an oxidant.

[0036] In a preferred embodiment of the present invention, the preparation method comprises the following steps:

[0037] (1) mixing alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina to obtain a mixed dry material;

[0038] (2) kneading the mixed dry materials into a mold and extruding them into granules;

[0039] (3) Drying the product of step (2) and performing the surface treatment to obtain the alumina carrier.

[0040] In a preferred embodiment of the present invention, the alumina powder includes pseudo-boehmite powder and optionally other alumina powders other than boehmite powder. By way of example, other alumina powders other than boehmite powder include, but are not limited to, the following alumina powders: one or more of γ-alumina, η-alumina, θ-alumina, χ-alumina, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, and hydrated alumina with a Bayerite structure.

[0041] In a preferred embodiment of the present invention, the molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch.

[0042] In a preferred embodiment of the present invention, the pore-forming agent is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol and sesbania powder.

[0043] In a preferred embodiment of the present invention, the inorganic compound is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite.

[0044] According to the present invention, the amount of each raw material can be selected within a wide range. In a preferred embodiment of the present invention, the amount of the inorganic carbon species is 1-40 parts by mass, for example, 1, 3, 5, 8, 10, 15, 20, 25, 30, 35, 40 parts, and any two values ​​or any interval between any two values, relative to 100 parts of alumina powder; and / or,

[0045] In parts by mass, relative to 100 parts of alumina powder, the amount of the molding agent is 1-15 parts, for example, 1, 3, 5, 8, 10, 15 parts, and any two values ​​or any interval between any two values; and / or,

[0046] In parts by mass, relative to 100 parts of alumina powder, the amount of the pore former is 1-15 parts, for example 1, 3, 5, 8, 10, 15 parts, and any two values ​​or any interval between any two values, and / or,

[0047] In parts by mass, relative to 100 parts of alumina powder, the amount of the inorganic compound is 0-30 parts, preferably 0-28 parts, such as 0, 5, 10, 15, 20, 23, 28 parts, and any two values ​​or any interval between any two values.

[0048] More preferably, the amount of the inorganic carbon species is 1-40 parts by mass relative to 100 parts of alumina powder; the amount of the forming agent is 1-15 parts by mass relative to 100 parts of alumina powder; the amount of the pore-forming agent is 1-15 parts by mass relative to 100 parts of alumina powder; the amount of the inorganic compound is 0-30 parts, preferably 0-28 parts, relative to 100 parts of alumina powder.

[0049] In a preferred embodiment of the present invention, the crystallization conditions include: 120-250° C., 4-18 h, 0.2-15 MPa, and / or the solvent is selected from at least one of water, ethanol, ethylene glycol, and ethylenediamine.

[0050] In a preferred embodiment of the present invention, the oxidation conditions include: 30-80°C, 0.2-10h, the oxidant is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant is 0.1-10 mol / L.

[0051] In a preferred embodiment of the present invention, the alkalization conditions include: 30-110° C., 0.2-10 h, the alkaline compound is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline compound is 0.1-10 mol / L.

[0052] In a preferred embodiment of the present invention, the irradiation radiation source is selected from gamma rays and / or microwaves; preferably: the gamma ray irradiation dose rate is 2-90 kGy / min, the time is 0.2-24 h; and / or, the microwave power is 50-1000 W; the time is 0.5-60 min.

[0053] In a preferred embodiment of the present invention, the inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, white carbon, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond.

[0054] According to the present invention, the surface treatment method is selected from at least one of heat treatment, crystallization, oxidation, alkalization and irradiation treatment.

[0055] The inventors of the present invention have discovered through research that the surface treatment method can be combined in the following ways to obtain an alumina carrier with a higher hydroxyl content and a higher total content of oxygen-containing groups: the surface treatment method is selected from: heat treatment; or, crystallization and oxidation; or, heat treatment and irradiation treatment; or, heat treatment and alkalization; or, heat treatment, alkalization and irradiation.

[0056] The inventors of the present invention have further discovered through research that different inorganic carbon species can be treated with specific surface treatment methods to obtain alumina supports with a further higher hydroxyl content and a further higher total content of oxygen-containing groups, as follows:

[0057] In a more preferred embodiment of the present invention, when the inorganic carbon species is coke, activated carbon, carbon black, white carbon, or glassy carbon, heat treatment is used; or, surface treatment is performed by crystallization and oxidation.

[0058] In a more preferred embodiment of the present invention, when the inorganic carbon species is charcoal, bamboo charcoal, or coconut shell charcoal, heat treatment is used; or, heat treatment and irradiation are used for surface treatment.

[0059] In a more preferred embodiment of the present invention, when the inorganic carbon species is graphene, graphyne, or diamond, the surface treatment is performed by crystallization and oxidation; or heat treatment and alkalization; or heat treatment, alkalization, and irradiation.

[0060] In a more preferred embodiment of the present invention, the solution used for kneading is an acidic solution, and preferably, the concentration of the acidic solution is 0.001-1 mol / L.

[0061] In a more preferred embodiment of the present invention, the solute in the acidic solution is selected from at least one of acetic acid, maleic acid, malic acid, citric acid, oxalic acid, formic acid, tartaric acid, ascorbic acid, salicylic acid, succinic acid, nitric acid, sulfuric acid, hydrochloric acid, hypochlorous acid, and phosphoric acid.

[0062] In a more preferred embodiment of the present invention, the solvent in the acidic solution is selected from water and / or a mixed solution of water and organic matter; more preferably, the organic matter is selected from methanol, ethanol, and ethylene glycol, and the volume ratio of the organic matter to water is (0.05-1.5):1.

[0063] The third aspect of the present invention is to provide an application of the alumina carrier described in the first aspect or the alumina carrier prepared by the preparation method described in the second aspect in a catalyst.

[0064] In a more preferred embodiment of the present invention, the catalyst contains a metal element.

[0065] According to the above technical scheme, the present invention introduces inorganic carbon species into the alumina carrier, and adopts surface treatment, wherein the surface treatment method is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment, wherein the heat treatment is carried out under specific conditions, and the oxidation is oxidation by an oxidant, which can cause different degrees of oxidation on the surface of the inorganic carbon species (different from the strong oxidation by simple calcination), thereby increasing the hydroxyl content and the total number of oxygen-containing groups:

[0066] The alumina carrier of the present invention has oxygen-containing groups on its surface, and the density of oxygen-containing groups on the surface of the alumina carrier is 0.15-5 mmol / m 2 , preferably 0.3-3mmol / m 2 ;

[0067] The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 10-150 m 2 / g, preferably 15-80m 2 / g.

[0068] It can be seen that the alumina carrier of the present invention not only has a high content of oxygen-containing groups, but also has relatively good physical properties, which can meet the requirements of industrial catalysts for physical properties such as strength and specific surface area. The regulation of the number and distribution of oxygen-containing groups on the surface of the alumina carrier of the present invention can well meet the various index requirements of various types of supported catalysts in the field of petrochemicals for the dispersion form and dispersion degree of different metal active components; it has high strength water absorption rate, large pore volume and most probable pore diameter, and has a benefit effect on the uniform distribution of active metal components in the catalyst loading process, and has extremely high application value. DETAILED DESCRIPTION

[0069] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0070] Example 1

[0071] Take the specific surface area of ​​150.3m 2100g pseudo-boehmite powder, 5g sesbania powder, 8g carboxymethyl cellulose, and 4g bamboo charcoal with a pore volume of 0.75ml / g and a bulk density of 0.22g / ml are mixed evenly. 1.8g concentrated nitric acid is added to 150g deionized water to prepare a mixed solution. The mixed solution is added to the mixed powders, and then put into a kneader to fully knead, and then extruded and granulated to obtain cylindrical particles with a particle size of 2-4mm, dried at 80℃ for 8h, and then heat treated with air and water vapor (volume ratio 0.8:1) at 1200℃ and 0.1MPa for 24h to obtain alumina carrier S1.

[0072] Example 2

[0073] Take the specific surface area of ​​150.3m 2 / g, pore volume 0.75ml / g, bulk density 0.22g / ml 100g pseudo-boehmite powder, 10g silicon oxide, 8g coconut shell carbon, 5g sesbania powder, 10g ethyl cellulose, mix well. Take 1.8g concentrated nitric acid, add it to 150g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm. Then heat treat it with air and water vapor (volume ratio 0.8:1) at 600℃ and 1.5MPa for 12h to obtain alumina carrier S2.

[0074] Example 3

[0075] Take the specific surface area of ​​160.4m 2 / g, pore volume 0.8ml / g, bulk density 0.16g / ml 20g alumina trihydrate powder, 80g α-Al2O3 powder, 6g polyethylene glycol, 7g methyl cellulose, 10g graphene, mix well. Take 4g oxalic acid and 4g acetic acid, add them into 150g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 80℃ for 8h, then crystallize them at 250℃, 15MPa for 4h, then soak them in a mixed solution of 5mol / L hydrogen peroxide and 5mol / L potassium permanganate at 30℃ for 0.2h, freeze-dry them at -20℃ for 4h to obtain alumina carrier S3.

[0076] Example 4

[0077] Take the specific surface area as 200.3m 2100g alumina trihydrate powder with a pore volume of 1.42ml / g and a bulk density of 0.15g / ml, 5g polyethylene glycol cellulose, 5g polyvinyl alcohol, and 12g graphyne are mixed evenly. Take 2.2g concentrated sulfuric acid and add it to 125g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 80℃ for 8h, heat treat them at 300℃, 3MPa carbon dioxide and nitrogen (volume ratio 0.5:1) for 1h, and then soak them in 5mol / L potassium carbonate solution, and then irradiate them with 2kGy / min of gamma rays for 24h to obtain alumina carrier S4.

[0078] Example 5

[0079] Take 120g pseudo-boehmite powder (physical properties are the same as in Example 1), 20g γ-Al2O3 powder, 10g fast-dealumina powder, 4.5g sesbania powder, 5g starch, 3.7g carbon black, and mix them evenly. Weigh 2.5g concentrated hydrochloric acid and 1.2g acetic acid, add them to 160g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 80℃ for 8h, then crystallize them at 120℃ and 0.2MPa for 18h, then soak them in a mixed solution of 0.1mol / L nitric acid and 0.1mol / L hydrogen peroxide at 80℃ for 10h, and freeze-dry them at -40℃ for 8h to obtain alumina carrier S5.

[0080] Example 6

[0081] Take 120g pseudo-boehmite powder (physical properties are the same as in Example 1), 20g γ-Al2O3 powder, 10g barium oxide, 5.8g cyanoethyl cellulose, 4.8g polypropylene glycol, 30g diamond, and mix them evenly. Weigh 6.9g ascorbic acid and 1.2g concentrated hydrochloric acid, add 175g ethanol and deionized water (volume ratio 5:1) solvent to prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 100℃ for 4h, heat treat them at 350℃, 0.2MPa acetylene and argon (volume ratio 0.05:1) for 3h, and then soak them in 0.1mol / L sodium hydroxide solution for 10h, and then irradiate them with 50W microwave for 60min to obtain alumina carrier S6.

[0082] Example 7

[0083] Take 120g of pseudo-boehmite powder (physical properties are the same as those in Example 1), 20g of calcium oxide, 9g of polyethylene glycol cellulose, 10g of polyvinyl alcohol, 6g of glassy carbon and 5g of coke, and mix them evenly. Take 1.8g of concentrated nitric acid and 2.2g of salicylic acid, add them to 150g of deionized water, and prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 80℃ for 8h, then crystallize them at 180℃, 7.5MPa for 11h, and then soak them in a mixed solution of 2.5mol / L ammonium persulfate and 2.5mol / L ascorbic acid at 55℃ for 5h to obtain alumina carrier S7.

[0084] Example 8

[0085] Take the specific surface area as 200.3m 2 100g alumina trihydrate powder with a pore volume of 1.42ml / g and a bulk density of 0.15g / ml, 1g hydroxypropyl cellulose and 1g polyacrylamide, 1g charcoal and 1g bamboo charcoal are mixed evenly. Take 3g concentrated hydrochloric acid and 3g hypochlorous acid, add them into 85g deionized water to prepare a mixed solution. Add the mixed solution to the mixed powders, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 80℃ for 8h, then crystallize them at 250℃ and 5MPa for 6h, and soak them in 5mol / L potassium bicarbonate and 5mol / L sodium bicarbonate solution for 0.2h to obtain alumina carrier S8.

[0086] Example 9

[0087] Take the specific surface area as 200.3m 2 100g of alumina trihydrate powder with a pore volume of 1.42ml / g and a bulk density of 0.15g / ml, 1g of hydroxypropyl cellulose and 1g of polyacrylamide, 1g of carbon black and 1g of white carbon black are mixed evenly. Take 3g of concentrated hydrochloric acid and 3g of hypochlorous acid, add them into 85g of deionized water to prepare a mixed solution. Add the mixed solution to the mixed powders, put them into a kneader and knead them thoroughly, then extrude and cut them into pellets to obtain cylindrical particles with a particle size of 2-4mm, dry them at 80℃ for 8h, heat treat them at 1200℃, 3MPa of methane and air (volume ratio 0.1:1) for 4h, and then irradiate them with 500W microwaves for 30min to obtain alumina carrier S9.

[0088] Comparative Example 1

[0089] Take 100g of pseudo-boehmite powder (physical properties are the same as those in Example 1), 5g of sesbania powder, 8g of carboxymethyl cellulose, and 4g of bamboo charcoal, and mix them evenly. Take 1.8g of concentrated nitric acid and add it to 150g of deionized water to prepare a mixed solution. Add the mixed solution to the mixed powders, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm. After drying and air heat treatment (the order, temperature, pressure, and time are the same as those in Example 1), the alumina carrier D1 is obtained.

[0090] Comparative Example 2

[0091] Take 100g of pseudo-boehmite powder (physical properties are the same as those in Example 2), 10g of silicon oxide, 5g of sesbania powder, and 10g of ethyl cellulose, and mix them evenly. Then take 1.8g of concentrated nitric acid and add it to 150g of deionized water to prepare a mixed solution. Add the mixed solution to the mixed powders, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm. After drying and heat treatment (the order and conditions are the same as those in Example 2), the alumina carrier D2 is obtained.

[0092] Comparative Example 3

[0093] Take the specific surface area of ​​160.4m 2 20g of alumina trihydrate powder with a pore volume of 0.8ml / g and a bulk density of 0.16g / ml, 80g of α-Al2O3 powder, 6g of polyethylene glycol, and 7g of methylcellulose are mixed evenly. 4g of oxalic acid and 4g of acetic acid are added to 150g of deionized water to prepare a mixed solution. The mixed solution is added to the mixed powders, and then put into a kneader to fully knead, and then extruded and granulated to obtain cylindrical particles with a particle size of 2-4mm. After drying, crystallization and oxidation (the order and conditions are the same as those in Example 3), an alumina carrier D3 is obtained.

[0094] Comparative Example 4

[0095] Take the specific surface area as 200.3m 2 100g of alumina trihydrate powder with a pore volume of 1.42ml / g and a bulk density of 0.15g / ml, 5g of polyethylene glycol cellulose, and 5g of polyvinyl alcohol are mixed evenly. 2.2g of concentrated sulfuric acid is added to 125g of deionized water to prepare a mixed solution. The mixed solution is added to the mixed powders, and then put into a kneader to fully knead, and then extruded and granulated to obtain cylindrical particles with a particle size of 2-4mm. After drying, heat treatment, alkalization and irradiation (the order and conditions are the same as those in Example 4), an alumina carrier D4 is obtained.

[0096] Comparative Example 5

[0097] Take 120g of pseudo-boehmite powder (physical properties are the same as in Example 1), 20g of γ-Al2O3 powder, 10g of barium oxide, 5.8g of cyanoethyl cellulose, and 4.8g of polypropylene glycol, and mix them evenly. Weigh 6.9g of ascorbic acid and 1.2g of concentrated hydrochloric acid, add 175g of ethanol and deionized water (volume ratio 5:1) as a solvent, and prepare a mixed solution. Add the mixed solution to the mixed powder, put them into a kneader and knead them thoroughly, then extrude and shape them into pellets to obtain cylindrical particles with a particle size of 2-4mm. After drying, heat treatment and alkalization (the order and conditions are the same as in Example 6), the alumina carrier D5 is obtained.

[0098] Comparative Example 6

[0099] Take the specific surface area as 200.3m 2 100g of alumina trihydrate powder with a pore volume of 1.42ml / g and a bulk density of 0.15g / ml, 1g of hydroxypropyl cellulose and 1g of polyacrylamide are mixed evenly. Take 3g of concentrated hydrochloric acid and 3g of hypochlorous acid, add them to 85g of deionized water to prepare a mixed solution. The mixed solution is added to the mixed powder, and then put into a kneader to fully knead, and then extruded and granulated to obtain cylindrical particles with a particle size of 2-4mm, dried at 80℃ for 8h, crystallized at 120℃, 0.2MPa for 18h, and then soaked in a mixed solution of 0.1mol / L nitric acid and 0.1mol / L hydrogen peroxide at 80℃ for 10h, and then heat-treated at 1200℃, 3MPa of methane and air (volume ratio 0.1:1) for 4h, and then soaked in 5mol / L potassium bicarbonate and 5mol / L sodium bicarbonate solution for 0.2h and irradiated with 500W microwave for 30min to obtain alumina carrier D6.

[0100] Comparative Example 7

[0101] Take the specific surface area of ​​150.3m 2 100g pseudo-boehmite powder, 5g sesbania powder, 8g carboxymethyl cellulose, 3g bamboo charcoal, 3g coconut shell carbon, 3g graphene, 3g graphyne, 3g carbon black, 3g diamond, 3g glassy carbon, 3g coke, 3g charcoal and 3g white carbon black with a pore volume of 0.75ml / g and a bulk density of 0.22g / ml are mixed evenly. 1.8g concentrated nitric acid is taken and added into 150g deionized water to prepare a mixed solution. The mixed solution is added into the mixed powder, and then put into a kneading machine together to fully knead, and then extruded and granulated to obtain cylindrical particles with a particle size of 2-4mm. After drying and air heat treatment (the order, temperature, pressure and time are the same as in Example 1), an alumina carrier D7 is obtained.

[0102] Test example

[0103] Physical property analysis and determination of the carriers of the embodiments and comparative examples: The specific surface area of ​​the carriers was measured by the nitrogen physical adsorption BET method;

[0104] Weigh 50 mL of the carrier to determine the bulk density of the carrier (take the arithmetic mean of three measurement results);

[0105] The pore volume and the most probable pore diameter of the support were measured by mercury intrusion method.

[0106] The carrier strength was measured using a particle strength meter (the arithmetic mean of the measurement results of 30 carriers was taken); 50 g of alumina carrier was weighed and soaked in water for 15 minutes, and the water absorption rate of the carrier was measured after draining the surface free water. The results are shown in Table 1.

[0107] Analysis and determination of oxygen-containing groups of carriers in the embodiments and comparative examples: The nature and quantity of oxygen-containing groups of carriers were determined by Boehm chemical method. Three 0.6g carrier samples were weighed and soaked in 40ml of 0.05mol / L NaHCO3, Na2CO3 and NaOH solutions for 24h respectively. 10ml of the soaking solution was titrated with 0.05mol / L hydrochloric acid. Each sample was titrated three times, and the arithmetic mean was taken. The number of various oxygen-containing groups of the carrier was calculated based on the consumption of alkali, and the oxygen-containing group density was obtained in combination with the carrier specific surface data. The results are listed in Table 2.

[0108] Table 1. Physical property measurement results of alumina carriers in Examples and Comparative Examples

[0109]

[0110] As can be seen from Table 1, the average particle strength of the alumina carrier prepared by the method of the present invention is greater than 45Nm and the bulk density is relatively low, indicating that this carrier is still applicable to most industrial catalyst loading requirements, and less active components are used when the catalyst loading volume is the same, which is conducive to reducing the catalyst cost. At the same time, the alumina carrier of the embodiment has a high water absorption rate, a large pore volume and a large most probable pore diameter, which has a benefit effect on the uniform distribution of active metal components during the catalyst loading process.

[0111] Table 2. Measurement results of oxygen-containing groups on alumina supports of Examples and Comparative Examples

[0112]

[0113] As described in the background art, studies have shown that the number or density of hydroxyl groups on the surface of alumina affects the dispersion form and degree of metal active components. Increasing the number of terminal hydroxyl groups can greatly improve the dispersion of metal elements on the carrier surface and even make them dispersed in a single atom.

[0114] As can be seen from Table 2, the hydroxyl content in the surface of the alumina carrier in the present invention is significantly higher than that in the comparative example, all of which are above 3mmol / g. In addition, the total content of oxygen-containing groups such as hydroxyl, carboxyl and lactone groups in the surface of the alumina carrier of the present invention is significantly higher than that in the comparative example, which can improve the adsorption strength of the carrier surface to the metal precursor and provide more metal particle anchoring sites, thereby slowing down the agglomeration or growth trend of metal particles in the subsequent catalyst preparation process (such as impregnation, drying, reduction, etc.), and achieving high dispersion of metal elements on the carrier surface. It can be seen from this that the present invention introduces inorganic carbon species into the alumina carrier, and then combines the subsequent surface treatment method to significantly increase the total content of oxygen-containing groups, especially significantly increase the hydroxyl content.

[0115] As shown in Examples 1-9, the introduction of inorganic carbon species to an alumina carrier, combined with a subsequent preferred treatment method, for example, the surface treatment method is selected from: heat treatment; or, crystallization and oxidation; or, heat treatment and irradiation treatment; or, heat treatment and alkalization; or, heat treatment, alkalization and irradiation, can significantly increase the total content of oxygen-containing groups, especially significantly increase the hydroxyl content.

[0116] From the comparison of Example 1, Example 2, and Example 8, it can be seen that when the inorganic carbon species is charcoal, bamboo charcoal, or coconut shell charcoal, heat treatment; or surface treatment by heat treatment and irradiation; can further increase the total content of oxygen-containing groups, especially significantly increase the hydroxyl content.

[0117] Generally speaking, the stronger the "anchoring" effect of the carrier on the metal particles, the higher its dispersion, but the metal may be coated by the carrier or the coordination is too stable, so that its adsorption and activation ability for the reactant molecules is significantly weakened or eliminated, and the catalytic performance is reduced. Therefore, for some catalysts, the higher the metal dispersion is, the better the catalytic performance is not necessarily. By comparing Example 5 and Example 9, it can be seen that when the inorganic carbon species is coke, activated carbon, carbon black, white carbon black, and glassy carbon, heat treatment, or crystallization and oxidation are used for surface treatment, which is a more preferred embodiment.

[0118] Experimental verification shows that when the inorganic carbon species is coke, activated carbon, carbon black, white carbon, or glassy carbon, surface treatment is performed by heat treatment, or crystallization and oxidation; when the inorganic carbon species is graphene, graphyne, or diamond, surface treatment is performed by crystallization and oxidation, or heat treatment and alkalization, or heat treatment, alkalization, and irradiation, which can further increase the total content of oxygen-containing groups, especially significantly increase the hydroxyl content.

[0119] In summary, it can be seen from Table 2 that the content and density of oxygen-containing groups on the surface of the alumina carrier prepared by the method of the present invention are significantly higher than those of the alumina carrier of the comparative example. At the same time, by adjusting the raw material ratio, preparation process parameters and conditions, the method of the present invention can achieve the regulation of the number and distribution of oxygen-containing groups on the surface of the alumina carrier, and can well meet the various index requirements of various types of supported catalysts in the field of petrochemicals for the dispersion form and dispersion degree of different metal active components.

[0120] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0121] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0122] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0123] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0124] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0125] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. An alumina carrier, wherein the surface of the alumina carrier has oxygen-containing groups, and the density of the oxygen-containing groups on the surface of the alumina carrier is 0.15-5 mmol / m 2 ; in, The oxygen-containing group is at least one of a hydroxyl group, a carboxyl group, and a lactone group; the specific surface area of ​​the alumina carrier is 10-150 m 2 / g.

2. The alumina carrier according to claim 1, characterized in that: The content of the hydroxyl group is 3-60 mmol / g; and / or, The content of the carboxyl group is 3-50 mmol / g; and / or, The content of the lactone group is 3-40 mmol / g.

3. The alumina carrier according to claim 1, characterized in that: The alumina support contains alumina and optionally an inorganic compound other than alumina; preferably, The inorganic compound is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite; and / or, The mass ratio of the inorganic compound to the aluminum oxide is (0-30):100, preferably (0-28):

100.

4. The alumina carrier according to claim 1, characterized in that: The water absorption rate of the alumina carrier is 50-200%; and / or, The strength of the alumina carrier is 30-200 Nm; and / or, The bulk density of the alumina carrier is 0.4-0.8 g / ml; and / or, The pore volume of the alumina carrier is 0.6-1.5 ml / g.

5. The alumina carrier according to any one of claims 1 to 4, characterized in that: The alumina support contains alumina and carbide; and / or, Based on the total weight of the alumina carrier being 100wt%, the content of the alumina is 50-98wt%; Preferably, the alumina carrier is prepared by the following preparation method, which comprises: The raw materials including alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina are granulated and surface treated to obtain the alumina carrier; Wherein, the surface treatment method is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment; The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; the oxidation is oxidation by an oxidant.

6. A method for preparing an alumina carrier, the preparation method comprising: The raw materials including alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina are granulated and surface treated to obtain the alumina carrier; Wherein, the surface treatment method is selected from at least one of heat treatment, crystallization, oxidation, alkalization, and irradiation treatment; The heat treatment conditions include: the heat treatment atmosphere includes a first atmosphere and a second atmosphere, the first atmosphere is selected from at least one of carbon dioxide, water vapor, acetylene, ethylene, and methane, the second atmosphere is selected from at least one of air, nitrogen, argon, and helium, the volume ratio of the first atmosphere to the second atmosphere is (0.05-1):1, the heat treatment temperature is 300-1200°C, the heat treatment time is 1-24h, and the pressure is 0.1-3MPa; the oxidation is oxidation by an oxidant.

7. The preparation method according to claim 6, characterized in that The preparation method comprises the following steps: (1) mixing alumina powder, a forming agent, a pore-forming agent, an inorganic carbon species and an optional inorganic compound other than alumina to obtain a mixed dry material; (2) kneading the mixed dry materials into a mold and extruding them into granules; (3) Drying the product of step (2) and performing the surface treatment to obtain the alumina carrier.

8. The preparation method according to claim 6, characterized in that: The alumina powder comprises pseudo-boehmite powder and optionally other alumina powders except the boehmite powder; and / or, The molding agent is selected from at least one of polyethylene glycol cellulose, methyl cellulose, carboxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, cyanoethyl cellulose, hydroxypropyl cellulose and starch; and / or, The pore-forming agent is selected from at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, polypropylene glycol and sesbania powder; and / or, The inorganic compound is selected from at least one of silicon oxide, magnesium oxide, barium oxide, calcium oxide and hydrotalcite.

9. The preparation method according to claim 6, characterized in that: In parts by mass, the amount of the inorganic carbon species is 1-40 parts relative to 100 parts of alumina powder; and / or, In parts by mass, the amount of the molding agent is 1-15 parts relative to 100 parts of alumina powder; and / or, In parts by mass, the amount of the pore former is 1-15 parts relative to 100 parts of alumina powder, and / or, In parts by mass, relative to 100 parts of alumina powder, the amount of the inorganic compound is 0-30 parts, preferably 0-28 parts.

10. The preparation method according to claim 6, characterized in that: The crystallization conditions include: 120-250° C., 4-18 h, 0.2-15 MPa, and / or, the solvent is selected from at least one of water, ethanol, ethylene glycol, and ethylenediamine; and / or, The oxidation conditions include: 30-80°C, 0.2-10h, the oxidant is selected from at least one of nitric acid, sulfuric acid, ammonium persulfate, hydrogen peroxide, potassium permanganate, and ascorbic acid, and the concentration of the oxidant is 0.1mol / L-10mol / L; and / or, The alkalization conditions include: 30-110°C, 0.2-10h, the alkaline compound is selected from at least one of sodium hydroxide, sodium bicarbonate, sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, potassium hydroxide, potassium bicarbonate, potassium carbonate, potassium acetate, and potassium citrate, and the concentration of the alkaline compound is 0.1mol / L-10mol / L; and / or, The irradiation source is selected from gamma rays and / or microwaves; preferably: the gamma ray irradiation dose rate is 2-90 kGy / min, the time is 0.2-24 h; and / or, the microwave power is 50-1000 W, and the time is 0.5-60 min.

11. The preparation method according to any one of claims 6 to 10, characterized in that: The inorganic carbon species is selected from at least one of coke, activated carbon, carbon black, white carbon, glassy carbon, charcoal, bamboo charcoal, coconut shell charcoal, graphene, graphyne, and diamond; and / or, The surface treatment method is selected from: heat treatment; or, crystallization and oxidation; or, heat treatment and irradiation treatment; or, heat treatment and alkalization; or, heat treatment, alkalization and irradiation; preferably, When the inorganic carbon species is coke, activated carbon, carbon black, white carbon, or glassy carbon, heat treatment is used; or, surface treatment is performed by crystallization and oxidation; When the inorganic carbon species is charcoal, bamboo charcoal, or coconut shell charcoal, heat treatment is used; or, surface treatment is performed by heat treatment and irradiation; When the inorganic carbon species is graphene, graphyne or diamond, the surface treatment is carried out by crystallization and oxidation; or heat treatment and alkalization; or heat treatment, alkalization and irradiation.

12. Use of the alumina carrier according to any one of claims 1 to 5, or the alumina carrier prepared by the preparation method according to any one of claims 6 to 11 in a catalyst; Preferably, the catalyst contains a metal element.

Citation Information

Patent Citations

  • Double-peak-pore-structured aluminum oxide supporter and preparation method thereof

    CN105983443A

  • Modified alumina carrier and preparation method thereof

    CN109420528A

  • Coal tar hydrotreating catalyst and preparation method thereof

    CN109926062A

  • Hydrogenation catalyst as well as preparation method and application thereof

    CN113559887A

  • Tableted alpha-alumina catalyst support

    CN115996792A

Cited By

  • Selective hydrogenation catalyst as well as preparation method and application thereof

    CN119633813A

  • A selection of hydrogenation catalysts, methods for their preparation and use

    CN119633813B

  • C3 and C4 full hydrogenation catalyst as well as preparation method and application thereof

    CN119657125A

  • A carbon three carbon four total hydrogenation catalyst, a preparation method and application thereof

    CN119657125B

  • C3 liquid phase selective hydrogenation catalyst as well as preparation method and application thereof

    CN119680535A